Problems of legal guarantees of workers’ rights in the field of working time, rest time and wages in the conditions of martial law - I. V. Nazarenko; K. Yu. Melnyk (Bulletin of Kharkiv National University of Internal Affairs)
The problems of legal guarantees of the rights of workers in the field of working time, rest time and wages in the conditions of martial law have been studied. The definition of the terms “legal guarantees of employee rights” and “employee” has been improved. Legal guarantees of employee rights are legal norms that ensure the realization and protection of the rights of an individual working on the basis of an employment contract, as well as the activities of authorized bodies and organizations for the implementation of these norms. An employee is a natural person who works on the basis of an employment contract.